Old wounds - Kelly, Nora (London : HarperCollins, 1998)
The rural campus of Stanton College, though within easy reach of New York, has remained free of violence-- until the discovery of a female student's body on a lonely country road.
Keywords: Deception -- United States -- Fiction. -- Women historians -- United States -- Fiction